2015
DOI: 10.1787/5js64kst5wvl-en
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Costs of Withdrawing Antimicrobial Growth Promoters from the Livestock Sector

Abstract: This paper is published under the responsibility of the Secretary-General of the OECD. The opinions expressed and the arguments employed herein do not necessarily reflect the official views of OECD member countries. The statistical data for Israel are supplied by and under the responsibility of the relevant Israeli authorities. The use of such data by the OECD is without prejudice to the status of the Golan Heights, East Jerusalem and Israeli settlements in the West Bank under the terms of international law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Consequently, some countries such as Mexico, New Zealand, and South Korea have adopted the EU approach. Other countries such as United States, Canada, or Japan have established guidelines and recommendations to reduce the use of AGP in animal productions (Laxminarayan et al, 2015; Brown et al, 2017; Liao and Nyachoti, 2017). To help fighting against antibiotic resistance, the international organizations have ruled through global action plans aimed at ensuring treatment and prevention of infectious diseases with safe and effective medicines (WHO, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, some countries such as Mexico, New Zealand, and South Korea have adopted the EU approach. Other countries such as United States, Canada, or Japan have established guidelines and recommendations to reduce the use of AGP in animal productions (Laxminarayan et al, 2015; Brown et al, 2017; Liao and Nyachoti, 2017). To help fighting against antibiotic resistance, the international organizations have ruled through global action plans aimed at ensuring treatment and prevention of infectious diseases with safe and effective medicines (WHO, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ban of antibiotics as AGPs is economically and negatively impacting the livestock sector because of different and uncontrolled bacterial diseases (Laxminarayan et al, 2015). To help control increasing resistance to antibiotics, innovative alternatives are urgently needed for food-animal production (Seal et al, 2013; Cheng et al, 2014; Kogut, 2014; Czaplewski et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Enforcement of regulations and voluntary uptake of recommended standards can be greatly enhanced by the provision of support measures, such as advisory services to farmers and insurance schemes that protect farmers from financial hardship while phasing out the use of antibiotics. This is particularly relevant in LMICs, where the withdrawal of antibiotics in food production, a low margin industry, is likely to have greater negative financial impacts compared to HICs, where management practices are generally better (Laxminarayan et al 2015).…”
Section: Agriculture and Foodmentioning
confidence: 99%
“…A review performed for OECD (Laxminarayan et al 2015) of the economic costs of banning antimicrobials for growth promotion use found that it is possible for pig and poultry producers to maintain production levels without antimicrobials through preventive management such as vaccination, segregation of animals by age, sanitary protocols, good ventilation systems, adjustment in feed rations, and physical external and internal biosecurity measures. Additional costs of production would be minor at around 1-2 percent in well-managed optimized livestock farms with up-to-date infrastructure.…”
Section: Husbandry and Managementmentioning
confidence: 99%
See 1 more Smart Citation